\(^n\)

\(9\cdot3^3\cdot\dfra...">

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 6 2022

`9.3^3 .1/81 .3^2 `

`= 9. 3^3/3^4 .3^2`

`= 9.1/3 .9 = 9/3 .3 = 3.3 =9 =3^2`

`4.2^5 :(2^3 .1/16)`

`= 4. 32 : (8/16)`

`= 4.32:1/2 = 4.32.2 = 256 = 2^8`

23 tháng 6 2022

1/

\(=3^2.3^3.\dfrac{1}{3^4}.3^2=3^3\)

2/

\(=2^2.2^5:\left(2^3.\dfrac{1}{2^4}\right)=2^7.2=2^8\)

18 tháng 6 2016

\(a,9.3^3.\frac{1}{81}.3^2=3^2.3^3.3^{\left(-4\right)}.3^2=3^{2+3-4+2}=3^3.\)

\(b,4.2^5:\left(2^3.\frac{1}{16}\right)=2^2.2^5:\left(2^3.2^{-4}\right)=2^{2+5}:2^{3-4}=2^7:2^{-1}=2^{7-\left(-1\right)}=2^8.\)

\(c,3^2.2^5.\left(\frac{2}{3}\right)^2=3^2.2^5.\frac{2^2}{3^2}=\left(\frac{3^2}{3^2}\right).\left(2^5.2^2\right)=1.2^{5+2}=2^7\)

\(d,\left(\frac{1}{3}\right)^2.\frac{1}{3}.9^2=\left(\frac{1}{3}\right)^2.\frac{1}{3}.\left(3^2\right)^2=\left(\frac{1}{3}\right)^{2+1}.3^4=\left(\frac{1}{3}\right)^3.\left(\frac{1}{3}\right)^{-4}=\left(\frac{1}{3}\right)^{3-4}=\left(\frac{1}{3}\right)^{-1}=3^1\)

a: \(5^3\cdot25^n=5^{3n}\)

\(\Leftrightarrow5^{3n}=5^3\cdot5^{2n}\)

=>3n=2n+3

hay n=3

b: \(a^{\left(2n+6\right)\left(3n-9\right)}=1\)

=>(2n+6)(3n-9)=0

=>n=-3 hoặc n=3

c: \(\dfrac{1}{3}\cdot3^n=7\cdot3^2\cdot3^4-2\cdot3^n\)

\(\Leftrightarrow3^n\cdot\dfrac{1}{3}+3^n\cdot2=7\cdot3^6\)

\(\Leftrightarrow3^n=3^7\)

hay n=7

17 tháng 10 2017

a)-2/3

b)5/48

c)8/9

17 tháng 10 2017

c,\(\dfrac{4^{30}.3^{43}}{2^{57}.27^{15}}=\dfrac{\left(2^2\right)^{30}.3^{43}}{2^{57}.\left(3^3\right)^{15}}=\dfrac{2^{60}.3^{43}}{2^{57}.3^{45}}=\dfrac{2^3}{3^2}=\dfrac{8}{9}\)

tính a) \(\left[\dfrac{0.8\div\left(\dfrac{4}{5}\cdot1025\right)}{0.64-1}+\dfrac{\left(1.08-\dfrac{2}{25}\right)\div\dfrac{4}{7}}{\left(6\dfrac{5}{7}-3\dfrac{1}{4}\right)\cdot2\dfrac{2}{17}}+\left(1.2\cdot0.5\right)\div\dfrac{4}{5}\right]\) b) \(\left(0.2\right)^{-3}\left[\left(-\dfrac{1}{5}\right)^{-2}\right]^{-1}+\left[\left(\dfrac{1}{2}\right)^{-3}\right]^{-2}\div\left(2^{-3}\right)^{-1}-\left(0.175\right)^{-2}\) c) \(2+\dfrac{1}{1+\dfrac{1}{2+\dfrac{1}{1+\dfrac{1}{2}}}}\) d)...
Đọc tiếp

tính

a) \(\left[\dfrac{0.8\div\left(\dfrac{4}{5}\cdot1025\right)}{0.64-1}+\dfrac{\left(1.08-\dfrac{2}{25}\right)\div\dfrac{4}{7}}{\left(6\dfrac{5}{7}-3\dfrac{1}{4}\right)\cdot2\dfrac{2}{17}}+\left(1.2\cdot0.5\right)\div\dfrac{4}{5}\right]\)

b) \(\left(0.2\right)^{-3}\left[\left(-\dfrac{1}{5}\right)^{-2}\right]^{-1}+\left[\left(\dfrac{1}{2}\right)^{-3}\right]^{-2}\div\left(2^{-3}\right)^{-1}-\left(0.175\right)^{-2}\)

c) \(2+\dfrac{1}{1+\dfrac{1}{2+\dfrac{1}{1+\dfrac{1}{2}}}}\)

d) \(\dfrac{1}{90}-\dfrac{1}{72}-\dfrac{1}{56}-\dfrac{1}{42}-\dfrac{1}{3}\)

e) \(\left(\dfrac{1}{3}\right)^{-1}-\left(-\dfrac{6}{7}\right)^0+\left(\dfrac{1}{2}\right)^2\div2\)

f) \(\dfrac{\dfrac{1}{3}-\dfrac{1}{7}-\dfrac{1}{13}}{\dfrac{2}{3}-\dfrac{2}{7}-\dfrac{2}{13}}\cdot\dfrac{\dfrac{3}{4}-\dfrac{3}{16}-\dfrac{3}{64}-\dfrac{3}{256}}{1-\dfrac{1}{4}-\dfrac{1}{16}-\dfrac{1}{64}}+\dfrac{5}{8}\)

g) \(\dfrac{1}{-\left(2017\right)\left(-2015\right)}+\dfrac{1}{\left(-2015\right)\left(-2013\right)}+...+\dfrac{1}{\left(-3\right)\cdot\left(-1\right)}\)

h) \(\left(1-\dfrac{1}{1\cdot2}\right)+\left(1-\dfrac{1}{2\cdot3}+...+\left(1-\dfrac{1}{2017\cdot2018}\right)\right)\)

3
7 tháng 10 2017

c)

Ta có :\(2+\dfrac{1}{1+\dfrac{1}{2+\dfrac{1}{1+\dfrac{1}{2}}}}\)

\(=2+\dfrac{1}{1+\dfrac{1}{2+\dfrac{1}{\dfrac{3}{2}}}}\) \(=2+\dfrac{1}{1+\dfrac{1}{2+\dfrac{2}{3}}}\) \(=2+\dfrac{1}{1+\dfrac{1}{\dfrac{8}{3}}}\) \(=2+\dfrac{1}{1+\dfrac{3}{8}}\) \(=2+\dfrac{1}{\dfrac{11}{8}}\) \(=2+\dfrac{8}{11}\) \(=\dfrac{30}{11}\)

7 tháng 10 2017

d) \(\left(\dfrac{1}{3}\right)^{-1}-\left(-\dfrac{6}{7}\right)^0+\left(\dfrac{1}{2}\right)^2:2\)

\(=3-1+\left(\dfrac{1}{2}\right)^2:2\)

\(=3-1+\dfrac{1}{4}:2\)

\(=3-1+\dfrac{1}{8}\)

\(=\dfrac{17}{8}\)

23 tháng 12 2018

\(a)\dfrac{1}{4}-\dfrac{3}{4}:\left(\dfrac{-5}{8}\right)\)

\(=\dfrac{1}{4}-\dfrac{3}{4}.\dfrac{-8}{5}\)

\(=\dfrac{1}{4}-\dfrac{-6}{5}\)

\(=\dfrac{5}{20}+\dfrac{24}{20}\)

\(=\dfrac{29}{20}\)

\(b)3-\left(\dfrac{-6}{7}\right)^0+\sqrt{\dfrac{1}{16}}:2\)

\(=3-1+\sqrt{\left(\dfrac{1}{4}\right)^2}:2\)

\(=2+\dfrac{1}{4}.\dfrac{1}{2}\)

\(=\dfrac{16}{8}+\dfrac{1}{8}\)

\(=\dfrac{17}{8}\)

\(c)\dfrac{9^5.2^6}{4^3.3^8}=\dfrac{\left(3^2\right)^5.2^6}{\left(2^2\right)^3.3^8}=\dfrac{3^{10}.2^6}{2^6.3^8}=3^2=9\)

23 tháng 12 2018

cảm ơn bạn

5 tháng 8 2017

Theo đề bài ta có:

\(B=\dfrac{-1^2.-2^2.....-100^2}{1.2.2.3.....99.100}\)

\(B=\dfrac{1^2.2^2.....100^2}{1.2.2.3.....99.100}\)

\(B=\dfrac{1.1.2.2......100.100}{1.2.2.3.....99.100}\)

\(B=\dfrac{1.2.3......100}{1.2.3.......99}.\dfrac{1.2.3......100}{2.3.4......100}\)

\(B=100\)